2013
DOI: 10.1158/1078-0432.ccr-12-2654
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Paclitaxel to EphA2-Expressing Cancer Cells

Abstract: Purpose YSA is an EphA2-targeting peptide that effectively delivers anti-cancer agents to prostate cancer tumors (1). Here, we report on how we increased the drug-like properties of this delivery system. Experimental Design By introducing non-natural amino acids, we have designed two new EphA2 targeting peptides: YNH, where norleucine and homoserine replace the two methionine residues of YSA, and dYNH, where a D-tyrosine replaces the L-tyrosine at the first position of the YNH peptide. We describe the detail… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(102 citation statements)
references
References 43 publications
7
95
0
Order By: Relevance
“…18,19 Recently, an ephrin mimicking amino acid sequence (YSA; YSAYPDSVPMMS) is a peptide identified to selectively target EphA2 receptor activation and cellular internalization. 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Recently, an ephrin mimicking amino acid sequence (YSA; YSAYPDSVPMMS) is a peptide identified to selectively target EphA2 receptor activation and cellular internalization. 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…Both YNH and dYNH were complexed with paclitaxel (YNH-PTX and dYNH-PTX, respectively) and evaluated both in vitro and in vivo for activity in human prostate and mouse renal cancer cells. dYNH-PTX displayed enhanced stability versus YSA-PTX or YNH-PTX in mouse serum with enhanced antitumor and antivascular activity as compared with vehicle or paclitaxel treatments (Wang et al, 2013). Moreover, these proof-of-principle studies support the concept of structurally modifying the EphA2 ligand to develop drug conjugates with potential to treat a variety of cancer types that display elevated EphA2 expression.…”
Section: Ephrin Receptor Targetingmentioning
confidence: 61%
“…Once the receptor is activated, the peptide and its attached drug are internalized into a lysosome, where the peptide is degraded and the drug is free to exert its toxic effects on the cell (Wang et al, 2012). Previous studies have shown that paclitaxel conjugated with these peptides shows increased efficacy in prostate and renal cancers (Wang et al, 2013).…”
Section: Ephrin Receptor Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hilchie et al [19] designed a analog of NRC-03 by replacing all the original amino acids with the corresponding D-amino acids, named [D]-NRC-03, which exhibited higher anticancer activity than NRC-03 due to the stability against human serum or trypsin [21]. Except D-amino acid, other unnatural amino acids also have been used to modify the anticancer peptide to increase their stability or bioactivity [22][23][24]. Anticancer peptide of…”
Section: Introductionmentioning
confidence: 99%